Contemporary screen time usage among children 9–10‐years‐old is associated with higher body mass index percentile at 1‐year follow‐up: A prospective cohort study. Issue 12 (28th June 2021) - Nagata, Jason M.; Iyer, Puja; Chu, Jonathan; Baker, Fiona C.; Gabriel, Kelley Pettee; Garber, Andrea K.; Murray, Stuart B.; Bibbins‐Domingo, Kirsten; Ganson, Kyle T.
Summary: Objective: There is a paucity of prospective research exploring the relationship among contemporary screen time modalities (e.g., video streaming, video chatting, texting and social networking) and body mass index (BMI) percentile. The objective of this study was to determine the prospective associations between screen time behaviours in a large and demographically diverse population‐based cohort of 9–10‐year‐old children and BMI percentile at 1‐year follow‐up. Methods: We analyzed prospective cohort data from the Adolescent Brain Cognitive Development (ABCD) Study ( N  = 11 066). Multiple linear regression analyses were conducted to estimate associations between baseline screen time behaviours (exposure) and BMI percentile at 1‐year follow‐up, adjusting for race/ethnicity, sex, household income, parent education, depression, binge‐eating disorder and baseline BMI percentile. Results: Each additional hour of total screen time per day was prospectively associated with a 0.22 higher BMI percentile at 1‐year follow‐up (95% CI 0.10–0.34) after adjusting for covariates. When examining specific screen time behaviours, each additional hour of texting ( B  = 0.92, 95% CI 0.29–1.55), video chat ( B  = 0.72, 95% CI 0.09–1.36) and video games ( B  = 0.42, 95% CI 0.06–0.78) was significantly prospectively associated with higher BMI percentile. Conclusions: Screen time is prospectively associated with a higher BMI percentile 1 year later among children 9–10 years old.